Evaluation of the Distribution and Elimination of Balanced Isotonic Crystalloid, 5% Hypertonic Saline, and 6% Tetrastarch 130/0.4 Using Volume Kinetic Modeling and Analysis in Healthy Conscious Cats - Yiew, Xiu Ting; Bateman, Shane W.; Hahn, Robert G.; Bersenas, Alexa M. E. (Frontiers in Veterinary Science, 2020)
This prospective, randomized, blinded, interventional cross-over study investigated the distribution, elimination, plasma volume expansion, half-life, comparative potency, and ideal fluid prescription of three commonly prescribed intravenous (IV) fluids in 10 healthy conscious cats using volume kinetic analysis that is novel to veterinary medicine. Each cat received 20 mL/kg of balanced isotonic crystalloid (PLA), 3.3 mL/kg of 5% hypertonic saline (HS), and 5 mL/kg of 6% tetrastarch 130/0.4 (HES) over 15 min on separate occasions. Hemoglobin concentration, red blood cell count, hematocrit, heart rate, and blood pressure were measured at baseline, 5, 10, 15, 20, 30, 40, 50, 60, and every 15 min until 180 min. Urine output was estimated every 30 min using point-of-care bladder ultrasonography. Plasma dilution derived from serial hemoglobin concentration and red blood cell count served as input variables for group and individual fluid volume kinetic analyses using a non-linear mixed effects model. In general, the distribution of all IV fluids was rapid, while elimination was slow. The half-lives of PLA, HS, and HES were 49, 319, and 104 min, respectively. The prescribed fluid doses for PLA, HS, and HES resulted in similar peak plasma volume expansion of 27–30%. The potency of HS was 6 times higher than PLA and 1.7 times greater than HES, while HES was 3.5 times more potent than PLA. Simulation of ideal fluid prescriptions to achieve and maintain 15 or 30% plasma volume expansion revealed the importance of a substantial reduction in infusion rates following initial IV fluid bolus. In conclusion, volume kinetic analysis is a feasible research tool that can provide data on IV fluid kinetics and body water physiology in cats. The rapid distribution but slow elimination of IV fluids in healthy conscious cats is consistent with anecdotal reports of fluid overload susceptibility in cats and warrants further investigation.